2023
DOI: 10.3390/biomedicines11051393
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Pathophysiological Overview of Intestinal and Systemic Diseases Associated with Pancreatic Disorders: Causality or Casualty?

Abstract: The relationship between chronic intestinal disease, including inflammatory bowel disease (IBD) and celiac disease (CelD), and pancreatic disorders has been little investigated. Although an increased risk of acute pancreatitis (AP), exocrine pancreatic insufficiency with or without chronic pancreatitis, and chronic asymptomatic pancreatic hyperenzymemia have been described in these patients, the pathogenetic link remains unclear. It may potentially involve drugs, altered microcirculation, gut permeability/moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…These findings demonstrated that pretreatment with AEUD or MESA reduced hyperamylasemia in DSS-treated rats. Increased permeability of the inflamed mucosa may be the cause of the pancreatic enzyme rise found in more severe or active disease; this is a mechanism previously suggested in persons with intestinal infarction who also have elevated serum amylase levels [54].…”
Section: Discussionmentioning
confidence: 85%
“…These findings demonstrated that pretreatment with AEUD or MESA reduced hyperamylasemia in DSS-treated rats. Increased permeability of the inflamed mucosa may be the cause of the pancreatic enzyme rise found in more severe or active disease; this is a mechanism previously suggested in persons with intestinal infarction who also have elevated serum amylase levels [54].…”
Section: Discussionmentioning
confidence: 85%
“…Chronic pancreatitis (CP) is a chronic inflammatory disease of the pancreas that could lead to irreversible damage to the pancreatic tissues and to associated exocrine and endocrine insufficiency [1][2][3][4][5]. The diagnosis of CP relies on a combination of image findings that indicate irreversible damage to the pancreas, such as calcification, stones, and duct stricture or dilation, along with manifested exocrine and endocrine dysfunctions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggested that CP is not a localized disease confined to the pancreas [2]. CP is associated with elevated systemic levels of inflammatory mediators such as interleukin-6, tumor necrosis factor-α, interleukin-8, and members of the interleukin-1 family [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation